MANAJEMEN HUMAS DAN INFORMASI DALAM MENGELOLA BERITA PADA WEBSITE UNIVERSITAS ISLAM NEGERI SUMATERA UTARA (WWW.UINSU.AC.ID) SEBAGAI MEDIA INFORMASI UNIVERSITAS - Rahmad Hidayah; Hasan Sazali; Sholihah Titin Sumanti (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
This research entitled is Public Relations and Information Management in Managing News on the Website of the State Islamic University of North Sumatra (www.uinsu.ac.id) as University Information Media. This research aims to see how Public Relations and Information of UIN North Sumatra manage the website as a medium of information of the University. The theory used is the management theory proposed by George R. Terry. In the stage of analyzing the data, the researcher uses a qualitative methodology with an analysis of the Georige R. Terry model approach in which management consists of Planning (Planing), Organizing (Organizin), Actuating (Actuating), and Supervision (Controlling) or abbreviated as POAC. Based on the findings, the researcher draws conclusions a) In planning, Public Relations and Information create a website to provide information about UINSU. b) At the organizing stage, Public Relations and Information manage the website by creating content and publishing it on the website. c) In the implementation stage, Public Relations and Information of UIN North Sumatra in managing the website is searching, creating and publishing news and releases about activities or related to UIN North Sumatra.